DIGITAL TWIN DRIVEN SMART CAMPUS DEVELOPMENT: CONCEPTS, CHALLENGES AND OPPORTUNITIES - Jusia Amanda Ginting; I Gusti Ngurah Suryantara; Raphael Benedict Manuel (ISTEK WIDURI, 2026)
This study aims to examine the development and implementation of digital twin technology in supporting smart campus ecosystems through a Systematic Literature Review approach. The study focuses on identifying technological trends, implementation opportunities, and various challenges that arise in the adoption of digital twin systems within higher education environments. The SLR method was conducted using the PRISMA framework to ensure a transparent and systematic article selection process. A total of 765 initial articles were identified from various academic databases with a publication range from 2015 to 2025. After undergoing the screening and selection process, 36 relevant articles were obtained for further analysis. The results show that digital twin technology has significant potential in supporting smart campus management through real-time monitoring of campus infrastructure, predictive maintenance of facilities, energy management optimization, and data-driven decision-making in university operations. In addition, this review also identifies several challenges in implementing digital twin systems, including data integration complexity, cybersecurity risks, high infrastructure investment requirements, and organizational readiness in facing digital transformation.